High temperature in situ SEM assessment followed by ex situ AFM and EBSD investigation of the nucleation and early growth stages of Fe-Al intermetallics. (15th July 2021) - Sapanathan, T.; Sabirov, I.; Xia, P.; Monclús, M.A.; Molina-Aldareguía, J.M.; Jacques, P.J.; Simar, A.
Abstract: A dedicated in situ heating setup in a scanning electron microscope (SEM) followed by an ex situ atomic force microscopy (AFM) and electron backscatter diffraction (EBSD) is used to characterize the nucleation and early growth stages of Fe-Al intermetallics (IMs) at 596°C. A location tracking is used to interpret further characterization. Ex situ AFM observations reveal a slight shrinkage and out of plane protrusion of the IM at the onset of IM nucleation followed by directional growth. The formed interfacial IM compounds were identified by ex situ EBSD . It is now clearly demonstrated that the θ-phase nucleates first prior to the diffusion-controlled growth of the η-phase. The θ-phase prevails the intermetallic layer. Graphical abstract: Image, graphical abstract